(untitled) (Coordinates of Public Administration, 2026)
The article examines the problems of ensuring the stability and resilience of Ukraine’s transport infrastructure in the context of full-scale war, and justi-fies the use of public-private partnerships (PPPs) as an effective tool for innovative development and post-war restoration of infrastructure systems. It has been determined that the economic stability of a state directly depends on the stability of its infrastructure elements, and transport infrastructure (TI), as a component of critical infrastructure, plays a key role in ensuring the country’s defence capability and the logistics of transporting strategically important cargo. Based on an analysis of contemporary scientific works and international experience, the meaning of the concepts of «economic stability», «infrastructure resilience», and «transport infrastructure resistance» is clarified, and their role in the system of public administration is specified. A systematisation of known models of public-private partnerships has been carried out based on criteria such as: distribution of functions between partners; sources of payment and income structure; transfer and distribution of risks; property rights; degree of life cycle integration; method of financing; duration of the transfer contract; scope of responsibilities and depth of transfer. Based on a comprehensive analysis of international practice, the possibilities and limitations of implementing various PPP models in the field of transport infrastructure in Ukraine have been identified, taking into account military threats, legal conditions and financial risks. A «recommendation matrix» has been developed for selecting the optimal PPP models for various transport infrastructure subsystems, and five key areas for its development have been identified: modernisation of the road network; integration of rail and urban transport; development of ports and terminals; digitalisation of the transport system; and restoration of aviation infrastructure. It has been substantiated that the application of PPPs can become a decisive factor in increasing the stability and resilience of the Ukrainian transport system, ensuring its adaptability, rapid recovery and ability to function in conditions of prolonged crises and challenges.